节，也是一种承传 ：以新山中秋园游会为个案研究 = Festival, a cultural heritage : a case study of the mid-autumn festival fair in Johor Bahru, Malaysia - 吴思霓 Goh, Sze Nee (2011)
本论文以新山中秋园游会为研究对象。中秋园游会是1980年代马来西亚华人对于国家文化官方论述的一种抵抗及凝聚华族群体的活动，其创意理念来自柔佛新山。在新山华人社会的努力推动下，中秋园游会不止成为新山文化品牌之一，也输出至全马来西亚及新加坡。随后另一庆中秋模式万盏华灯庆中秋的出现，突破过去园游会的空间局限，其分散特性淡化了族群文化，但加强社区的凝聚。尽管中秋园游会的影响足以证明节庆文化再造的成功，并正面回应1990年代部分马华学者对于马华表演性的批评，仍有其缺点，故本文也通过文献与访问法来引起对活动未来走向的省思。This study focuses on the Mid-Autumn Festival Fair in Johor Bahru. The idea of this activity was initiated by the Chinese community in Johor Bahru in the 1980s, aiming to enhance the Chinese cohesion to resist the official narrative of the national cultural premised on the Malays With the effort of Johor Bahru Chinese community, the Mid-Autumn Festival Fair not only became one of the main attractions in Johor Bahru but also spread to the rest of Malaysia and even Singapore. The subsequent Johor Bahru Mid-Autumn Lantern Festival broke through the spatial constraints, diluting the ethnic culture but strengthening the communal cohesive. Although the activities show success in reinventing the culture and give answer to the criticism by some scholars in the 1990s, they have limitations. Drawing on printed materials and interviews, this study invites contemplation on the future direction of the activities.